Targeted treatment of severe vascular malformations harboring PIK3CA and TEK mutations with alpelisib is highly effective with limited toxicity - Sterba, Martin; Pokorna, Petra; Faberova, Renata; Pinkova, Blanka; Skotakova, Jarmila; Seehofnerova, Anna; Blatny, Jan; Janigova, Lucia; Koskova, Olga; Palova, Hana; Mahdal, Michal; Pazourek, Lukas; et al. (Scientific reports, 2023)
This was a prospective cohort study of eighteen patients with large and debilitating vascular malformations with one or more major systemic complications. In all patients, we discovered activating alterations in either TEK or PIK3CA. Based on these findings, targeted treatment using the PI3K inhibitor alpelisib was started with regular check-ups, therapy duration varied from 6 to 31 months. In all patients, marked improvement in quality of life was observed. We observed radiological improvement in fourteen patients (two of them being on combination with either propranolol or sirolimus), stable disease in 2 patients. For 2 patients, an MRI scan was not available as they were shortly on treatment, however, a clinically visible response in size reduction or structure regression, together with pain relief was observed. In patients with elevated D-dimer levels before alpelisib administration, a major improvement was noted, suggesting its biomarker role. We observed overall very good tolerance of the treatment, documenting a single patient with grade 3 hyperglycemia. Patients with size reduction were offered local therapies wherever possible. Our report presents a promising approach for the treatment of VMs harboring different targetable TEK and PIK3CA gene mutations with a low toxicity profile and high efficacy.
Keywords: fosfatidylinositol-3-kinasy třídy I; mutace; Phosphatidylinositol 3-Kinases; Humans; Mutation; prospektivní studie; lidé; Class I Phosphatidylinositol 3-Kinases; fosfatidylinositol-3-kinasy; kvalita života; Quality of Life; Prospective Studies